1994
DOI: 10.1007/bf00189311
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of neuropathic lesions in diabetic and alcoholic patients

Abstract: Cardiovascular reflex tests are used extensively to screen diabetic patients for autonomic cardiac neuropathy. Since alcohol abuse must often be considered the cause of nerve damage in internally ill patients, we examined 66 nonalcoholic type 1 (insulin-dependent) diabetics and 63 nondiabetic alcoholics matched for age, weight, and duration of disease to determine whether specific patterns of complaints, symptoms, signs, and results of the cardiovascular reflex tests can differentiate between alcoholic and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In males, erectile dysfunction appears to be a common feature affecting between 2-29% of chronic alcohol abusers [21,25,29,30]. The relationship between alcohol abuse and erectile dysfunction was explored in greater detail by Wetterling et al who found that there was increasing frequency of this symptom with increased alcohol consumption [31].…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In males, erectile dysfunction appears to be a common feature affecting between 2-29% of chronic alcohol abusers [21,25,29,30]. The relationship between alcohol abuse and erectile dysfunction was explored in greater detail by Wetterling et al who found that there was increasing frequency of this symptom with increased alcohol consumption [31].…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…The relationship between alcohol abuse and erectile dysfunction was explored in greater detail by Wetterling et al who found that there was increasing frequency of this symptom with increased alcohol consumption [31]. The wide range of the reported prevalence of erectile dysfunction in alcohol abusers was in part due to the various lengths of time between alcohol withdrawal and the commencement of the study [30]. Whilst the frequency of erectile dysfunction in this patient cohort varies significantly between studies, it is consistently the most common symptom reported.…”
Section: Erectile Dysfunctionmentioning
confidence: 99%